2020
DOI: 10.1002/smtd.202000029
|View full text |Cite
|
Sign up to set email alerts
|

Direct Nano‐Synthesis Methods Notably Benefit Mg‐Battery Cathode Performance

Abstract: Rechargeable magnesium batteries are promising candidates for nextgeneration electrochemical energy storage, but their development is severely hindered by sluggish solid-state diffusion and significant desolvation penalties of the divalent cation. Studies suggest that nano-sized electrode materials alleviate these issues by shortening diffusion lengths and increasing electrode/electrolyte interaction. Here, the effect of particle size and synthetic methodology on the electrochemical performance of four sulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 70 publications
(80 reference statements)
1
25
0
Order By: Relevance
“…These performance data reinforce the importance of interlayer expansion to facilitate Mg 2+ intercalation [34] and of nanostructuring to shorten Mg 2+ diffusion path inside the cathode. [18,103] Copper selenides were also studied to some extent. A cathode material of current interest is Cu 3 Se 2 due to its Cu +mediated cathode chemistry.…”
Section: Copper Chalcogenidesmentioning
confidence: 99%
See 2 more Smart Citations
“…These performance data reinforce the importance of interlayer expansion to facilitate Mg 2+ intercalation [34] and of nanostructuring to shorten Mg 2+ diffusion path inside the cathode. [18,103] Copper selenides were also studied to some extent. A cathode material of current interest is Cu 3 Se 2 due to its Cu +mediated cathode chemistry.…”
Section: Copper Chalcogenidesmentioning
confidence: 99%
“…have shown that nanodimensional layered TiS 2 achieves more stable capacity retention as compared to micrometer‐sized TiS 2 because the smaller grains minimize cation trapping within the lattice and mitigate the volume change during cycling. [ 103 ] Micrometer‐sized TiS 2 exhibited large irreversible capacity (47%) during the initial cycle and a reversible capacity of 160 mAh g −1 at C/40 (1C = 1 Mg 2+ /TiS 2 ) and 60 °C. [ 39 ] This implies that there is substantial cation trapping in the cathode host.…”
Section: Rmb Performance With Nanostructured Metal Chalcogenide Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The third is drastically decreasing the particle size of the electrodes. [ 192–195 ] As reported in LIBs and NIBs, the nanostructured materials have several important advantages compared with the bulk ones, such as increased contact interface of electrolyte and electrode, and shorter diffusion lengths for electrons and ions. [ 196–199 ] In RMBs, using nanostructured composites is also an effective way to obtain a decreased route for Mg 2+ diffusion with better performance.…”
Section: Optimization Strategiesmentioning
confidence: 99%
“…The third is drastically decreasing the particle size of the electrodes. [192][193][194][195] As reported in LIBs and NIBs, the nanostructured materials have several important advantages compared with the bulk ones, such as increased contact interface of electrolyte and electrode, and shorter diffusion lengths Figure 17. a) High energy XRD patterns of TiS 2 at different stages (stages 0-3 corresponding to the pristine TiS 2 , discharged to 1, 0.2, and 0 V, respectively).…”
Section: Nanostructure Constructionmentioning
confidence: 99%